A review of knowledge hiding in team: Evaluation of critical research streams - Muhammad Ashraf, Fauzi (Emerald Group, 2022)
Purpose; The purpose of this paper is to systematically review knowledge hiding (KH) behaviors in the team context. KH behavior is regarded as unethical and antisocial behavior, detrimental to team development and performance. The nature of its existence should not be allowed in team activities. Design/methodology/approach: Applying a systematic literature review, this study investigated 39 related quantitative studies on KH behavior of employees in team and group contexts. This study discusses the fundamental concept of KH, analyzes current research findings, identifies relevant gaps in the team and group context and sheds light on future direction. Findings: Findings observed that the KH phenomena had gained the interest of scholars since the year 2010. Five main research streams identified in this systematic review are role of leadership, team creativity and innovation, underlying theory, multilevel modeling and KH scale. Research limitations/implications: The value of this paper is subjected to the specific notion of KH in team background where knowledge sharing should have been promoted instead of KH. This systematic review serves as insight and recognition on the importance of mitigating KH in team. Existing current literature, future research work and trends of KH in the organization may benefit from this new and anticipated behavior within the knowledge management field. Originality/value: To the best of the authors’ knowledge, this review is the first to review KH behavior in the team context.